Pediatric myringoplasty – retrospective analysis over a 5-year period - Seixas, João (2022)
Objectives: Myringoplasties are frequently performed in pediatric patients, but there is still controversy regarding the best surgical technique and factors influencing its success. The aim of this study is to characterize a population of pediatric patients undergoing myringoplasty and evaluate the following outcomes: perforation closure, audiometric results and factors affecting surgical success. Study Design: Descriptive retrospective study Material and Methods: We evaluated 56 patients (57 ears) with a mean age of 10.4±3.2 years (6-17 years) over a 5-year period (2016-2020) Results: Most perforations occurred after grommet insertion. Retroauricular approach and underlay temporal fascia graft placement technique was used in most cases, with a success rate of 74% after a mean follow-up of 30 months. Pure tone average improved after the procedure. Craniofacial malformations were associated with incomplete air-bone gap closure. Conclusions: Pediatric myringoplasty has a high success rate.